Oral mycobiome in community‐dwelling elderly and its relation to oral and general health conditions. (13th June 2017) - Zakaria, MN; Furuta, M; Takeshita, T; Shibata, Y; Sundari, R; Eshima, N; Ninomiya, T; Yamashita, Y
Abstract : Objective: Oral fungal infection is generally associated with dysbiosis related to antibiotic use, immunodeficiency, or frailty. However, fungal colonization in a typical population without apparent symptoms and its associated conditions are poorly understood. In this study, oral fungal colonization in community‐dwelling and independently living elderly populations was evaluated and factors affecting fungal colonization were analyzed. Subjects and Methods: The subjects (410; 181 males and 229 females) were 75–99 years of age; those under prior antibiotic use were excluded. Fungal populations in the saliva were evaluated by PCR‐based molecular techniques. Body mass index (BMI), smoking habits, and oral health conditions were examined. Results: Salivary fungal amounts exceeded 10 4 CFU/ml in 63 (15.4%) of 410 subjects. Candida albicans was most frequently detected (98.4%), followed by Candida glabrata (54.0%), and Candida dubliniensis (38.1%) in those subjects with fungi at 10 4 CFU/ml or over. Fungi at 10 4 CFU/ml or over in the presence of C. glabrata or C. dubliniensis was significantly associated with low BMI. Conclusions: Candida albicans, C. glabrata, and C. dubliniensis dominated the oral mycobiome in Japanese community‐dwelling elderly. Lower BMI might signify compromised health status and thus could result in susceptibility to specific candidiasis by C. glabrata and C. dubliniensis .